Static equilibrium paths of steel-concrete composite beam strengthened under load = Ścieżki równowagi statycznej stalowo-betonowej belki zespolonej wzmacnianej pod obciążeniem - Szewczyk, Piotr; Szumigała, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents exemplary static equilibrium paths of an element strengthened while under load. A steel-concrete composite beam was analyzed. The study discusses the effect of strengthening method, initial load values, welding stress, concrete shrinkage and introduction of additional control of distortion state on the course of static equilibrium path. Results calculated in numerical FEM simulation were verified with experimental data and were found to be consistent.
Keywords: strengthening; composite beams; residual stresses; distortions; FEM; wzmocnienia; belka zespolona; naprężenia rezydualne; dystorsje; MES